Greice Schneider. What Happens When Nothing Happens: Boredom and Everyday Life in Contemporary Comics. Leuven: Leuven UP, 2016. - David Pinho Barros (Studies in 20th & 21st Century Literature, 2017)
Review of Greice Schneider. What Happens When Nothing Happens: Boredom and Everyday Life in Contemporary Comics. Leuven: Leuven UP, 2016.
Keywords: Comics studies; Narratology; Phenomenology; Aesthetics; Boredom